UNFUELED POWER SUPPLY FOR ISOLATED BASES ON SEA ICE - TERRY,C.W. (1961)
The feasibility of an unfueled power supply for use at isolated bases on sea ice was considered. Three sources of power which do not require fuel were investigated to determine whether their use might be practical: (1) the temperature differential between the water under sea ice and the air above the ice, (2) wind-driven generators, and (3) solar energy cells. A review of theoryAND THE RESULTS OF A LABORATORY TEST SHOWED THAT A DEVICE DEPENDING ON TEMPERATURE DIFFERENTIAL IS NOT A PRACTICAL ANSWER BECAUSE OF ICE FORMATION ON THE EVAPORATOR. A literature search showed that windmills have been used satisfactorily under somewhat similar circumstances; it appears that they would give adequate power for at least part of the bases under consideration. The literature search also showed that solar energy cells should operate satisfactorily during the seasons having long hours of sunlight. A further study of these two possibilities is recommended. (Author)